This thing called the future : a novel - Powers, J. L. (Jessica Lynn), 1974- (El Paso, TX : Cinco Puntos Press, 2011)
Fourteen-year-old Khosi's mother wants her to get an education to break out of their South African shantytown, although she herself is wasting away from an untreated illness, while Khosi's grandmother, Gogo, seeks help from a traditional Zulu healer.
Keywords: Sick -- Fiction; Healers -- Fiction; Medical care -- Fiction; Mothers and daughters -- Fiction; Zulu (African people) -- Fiction; Blacks -- South Africa -- Fiction; South Africa -- Fiction